Cycling to work: Meanings and experiences of a sustainable practice. (May 2019) - Rérat, Patrick
Highlights: Cycling to work is not only utilitarian; meanings and experiences are crucial. Motivations refer to well-being, independence and civic engagement. Four types of cyclists are identified: active, civic, independent and enthusiast. Barriers relate to safety, logistic constraints and comfort. Policy could integrate these dimensions into communication, road regulation and planning. Abstract: This paper draws on Cresswell's conceptualisation of mobility as a combination of physical movement, meaning, and embodied and experienced practice. It addresses the motivations of and barriers to cycling to work in Switzerland based on a large questionnaire survey (n = 13, 700). Motivations to cycle to work refer to well-being (both physical and mental), independence and civic engagement. Four types of cyclist are identified according to their motivations: active, civic, independent and enthusiast. Barriers relate to weather conditions, safety, logistical constraints and comfort. A cycling policy could integrate these results and focus on movement (a network of direct and well-maintained routes), experience (safe and pleasant routes designed for all types of cyclist) and meanings (by promoting cycling to various audiences and assessing the legitimacy of cycling as a fully-fledged means of transportation).